2016
DOI: 10.1124/dmd.116.072264
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporter 2: An Enigmatic Human Solute Carrier

Abstract: As a member of the solute carrier 22A (SLC22A) family, organic anion transporter 2 (OAT2; SLC22A7) is emerging as an important drug transporter because of its expression in both the liver and kidney, two major eliminating organs, and its ability to transport not only a wide variety of xenobiotics but also numerous physiologically important endogenous compounds, like creatinine and cGMP. However, OAT2 has received relatively little attention compared with other OATs and solute carriers (SLCs), like organic cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 90 publications
0
49
0
Order By: Relevance
“…For OAT2, interesting results have recently been reported. For details on OAT2, the reader may refer to an excellent, recent review (Shen et al, 2017b). Ciarimboli et al (2012) found significant OAT2-mediated creatinine uptake.…”
Section: Biomarkers For Function Of Renal Cation Transporters (Orgmentioning
confidence: 99%
See 1 more Smart Citation
“…For OAT2, interesting results have recently been reported. For details on OAT2, the reader may refer to an excellent, recent review (Shen et al, 2017b). Ciarimboli et al (2012) found significant OAT2-mediated creatinine uptake.…”
Section: Biomarkers For Function Of Renal Cation Transporters (Orgmentioning
confidence: 99%
“…6b-Hydroxycortisol is not transported by OAT1 and P-glycoprotein (Imamura et al, 2013) (Table 2). 6b-Hydroxycortisol is also a substrate of MATE1 and, with a low transport rate, of Tamai et al, 1998;Yabuuchi et al, 1999;Enomoto et al, 2002;Tanihara et al, 2007;Lancaster et al, 2010;Palmieri, 2013;Kato et al, 2014;Wu et al, 2015;Giangregorio et Urakami et al, 2004;Masuda et al, 2006;Tanihara et al, 2007;Imamura et al, 2011;Ciarimboli et al, 2012;Lepist et al, 2014;Shen et al, 2015Shen et al, , 2017bChu et al, 2016;Mathialagan et al, 2017 Dopamine c Catecholamine, neurotransmitter…”
mentioning
confidence: 99%
“…Emphasis has been given to hepatic uptake clearance mediated by organic anion transporting polypetides (OATPs), where many high-molecular-weight acids/zwitterions (ECCS class 1B/3B) are shown to be substrates (Giacomini et al, 2010;Shitara et al, 2013;Varma et al, 2015Varma et al, , 2017b. OAT2, a member of solute carrier 22A (SLC22A7), is expressed in the liver and kidney and is known to transport several xenobiotics and endogenous compounds (e.g., creatinine and cGMP) (Lepist et al, 2014;Shen et al, 2017). Although protein abundance of OAT2 in the human liver is relatively similar to that of other major uptake transporters, such as OATP1B, Na1-taurocholate cotransporting polypeptide, and organic cation transporter (OCT)1 (Nakamura et al, 2016;Vildhede et al, 2018), little is known about its role in the clinical pharmacokinetics of drugs (Shen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, PAH showed no competition with uptake of indomethacin, cGMP, or cAMP. Earlier studies claimed that PAH was a hOAT2 substrate but a recent review questions this (Shen, Lai, & Rodrigues, ).…”
Section: Discussionmentioning
confidence: 99%